City educational spaces (EECI’s) as an urban revitalization startegy in Sector I, IV and VI of the high district of the Alliance: San Juan de Dios School Park - Rojas Figueroa, Fernando Alonso (2017)
Objective: The objective of the research is to propose the Educativa Spaces of City (ESC's) as a strategy for urban revitalization and to develop the "School Park San Juan de Dios" as articulating and strategic centrality in sectors I, IV and VI of the Alto de la Alianza district. Method: The methodology used in the research was descriptive-analytical propositive, studying the situation of the Urban Voids, educational, recreational and cultural spaces in Alto de la Alianza district; in order to formulate an urban study that led to the urban revitalization proposal and later architectural proposal. Results: As a result of the research was developed an Urban Revitalization Proposal based on a network of Educativa Spaces of City or ESC's, which are cells equipped with educational, cultural, recreational and social uses, within which the conception of one defined as priority: the "School Park San Juan de Dios". Conclusions: From the aboye results, we can conclude that urban voids are abandoned spaces with great opportunities for revitalization, but if these are islands without connection or articulation, it will not be possible to integrally revitalize the study sector. Therefore, revitalizing the urban voids means revitalize their immediate environment too. Likewise, it is not enough to create spaces with educational uses, but it is also necessary to equip them with public, social, cultural and recreational space, being these decisive factors for the operation of its main characteristic; its relationship and connection to the city, which is presented as the main agent, environment and educational contentthat has the population.